A retrospective study of venous thromboembolism in acute leukemia patients treated at the University of Texas MD Anderson Cancer Center. (8th December 2014) - Vu, Khanh; Luong, Nhiem V.; Hubbard, Julie; Zalpour, Ali; Faderl, Stefan; Thomas, Deborah A.; Yang, Daisy; Kantarjian, Hagop; Kroll, Michael H.
Abstract The purpose was to determine the incidence and prevalence of venous thromboembolism (VTE) in acute leukemia patients from our institution. We conducted a retrospective study on newly diagnosed acute leukemia patients who presented at our institution from November 1999 to May 2005. Descriptive statistics and cross‐tabulation were used to describe patient characteristics. Measures of morbidity were used to address VTE risk. Chi‐square testing, Fisher's exact testing, Mann–Whitney analyses, or median testing were used to determine between‐group differences. Data analyses were conducted using Stata version 11 (Stata Corp., College Station, TX). Two hundred and ninety‐nine patients with acute lymphoblastic leukemia (ALL) and 996 patients with acute myeloid leukemia (AML) were included. After excluding patients diagnosed with VTE prior to or at the time of leukemia diagnosis, during the mean time follow‐up period of 2.5 years (range: 0.0025–10.3 years), the overall incidence rate of VTE was 3.7 per 100 person‐years: 4.2 per 100 person‐years for ALL and 3.4 per 100 person‐years for AML. Among all patients, the majority (80.6%) developed VTE within 12 months after diagnosis and during thrombocytopenia. The most common VTE was central venous catheter (CVC)‐associated upper‐extremity deep venous thrombosis. Pulmonary embolism occurred in 15% of ALL patients and 8% of AML patients. VTE recurred in 20.7% of ALL patients and 18.6% of AML patients. VTE occurs frequently in patients with acute leukemia. Studies are needed to identify risk factors for the development and recurrence of VTE among patients with acute leukemia and to establish more effective methods for preventing and treating VTEs in leukemia patients who have thrombocytopenia and/or CVC.